2008
DOI: 10.1176/jnp.2008.20.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury, Apolipoprotein E-ϵ4, and Cognition in Older Adults: A Two-Year Longitudinal Study

Abstract: Patients with mild-to-moderate traumatic brain injury (TBI) (N=69) were compared with age-, gender-, and education-matched healthy control group subjects (N=79) on performance of neuropsychological tests at one and 2 years following injury, and informant-rated functional abilities. All subjects were assessed for the presence of the Apolipoprotein E-epsilon4 (APOE-epsilon4) allele and rated for "mild cognitive impairment" (MCI) or dementia. Traumatic brain injury patients were no different from the comparison g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…However, the details of how TBI associates with the onset of cognitive impairment is still unclear due to a number of factors such as varied criteria for defining TBI severity [2], as well as various types and severity of cognitive impairment. A history of TBI has been found to correlate with an elevated risk for developing cognitive impairment [37]. For example, a 5-year follow-up study found that TBI could increase the risk of developing dementia by 1.7 fold after adjusting for covariates [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the details of how TBI associates with the onset of cognitive impairment is still unclear due to a number of factors such as varied criteria for defining TBI severity [2], as well as various types and severity of cognitive impairment. A history of TBI has been found to correlate with an elevated risk for developing cognitive impairment [37]. For example, a 5-year follow-up study found that TBI could increase the risk of developing dementia by 1.7 fold after adjusting for covariates [8].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, many studies reporting a lack of association between TBI and dementia have relied upon self-report 1,2,33 (raising concern for recall bias), have used a report of “head injury” 35 to approximate a history of TBI (raising concern for misdiagnosis), or have provided insufficient longitudinal follow-up. 2,14 …”
Section: Discussionmentioning
confidence: 99%
“…13 Even among studies reporting a positive association between TBI and dementia, there is dramatic variability in the magnitude of reported risk, which may be due to differences in TBI severity, age of subjects, and follow-up period (with some being as short as two years) between studies. 2,14 …”
Section: Introductionmentioning
confidence: 99%
“…At a system level, diffuse axonal injury may lead to increased vulnerability to N-methyl-D-aspartate toxicity (Arundine et al, 2004;Wolf et al, 2001), but brain injury severity may not be related to the apolipoprotein E-4 allele (Rapoport et al, 2008). In microdialysis studies of four TBI patients who had catheters in the area of the cranial bone flap and in the frontal lobe, the lesion site had higher FDG-PET metabolic rates and higher lactate and pyruvate than the frontal lobe site (Hutchinson et al, 2009).…”
Section: Regional Effectsmentioning
confidence: 98%